2012
DOI: 10.3329/jesnr.v5i1.11573
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Regeneration of High Yielding Indica Rice (Oryza sativa L.) Varieties

Abstract: The experiment was conducted to observe the regeneration potential and also to establish a suitable in vitro plantlet regeneration protocol from mature seed derived embryogenic calli of four indica rice varieties viz BRRI dhan28, BRRI dhan29, BRRI dhan47 and Binadhan-7 after partial desiccation treatment. Different concentrations and combinations of growth regulators were used in MS medium to observe the callus induction ability using mature embryo as explants. The percentage of callus induction frequency was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 6 publications
2
8
0
Order By: Relevance
“…Results indicated that 2 mgl -1 2,4-D with 0.1mgl -1 Kinetin or BAP was the most appropriate combination for callus induction. This fi nding agrees with the previous studies documented by Revathi et al, (2011), Alam et al, (2012), Dahanayake and Ranawake, (2012), Mannan et al,(2013), Dissanayaka and Dahanayaka, (2014), and Upadhya et al, (2015). The Journal of Agricultural Sciences -Sri Lanka , 2019, Vol.14, No.…”
Section: Callus Inductionsupporting
confidence: 92%
“…Results indicated that 2 mgl -1 2,4-D with 0.1mgl -1 Kinetin or BAP was the most appropriate combination for callus induction. This fi nding agrees with the previous studies documented by Revathi et al, (2011), Alam et al, (2012), Dahanayake and Ranawake, (2012), Mannan et al,(2013), Dissanayaka and Dahanayaka, (2014), and Upadhya et al, (2015). The Journal of Agricultural Sciences -Sri Lanka , 2019, Vol.14, No.…”
Section: Callus Inductionsupporting
confidence: 92%
“…30 Approximately similar increment of regeneration was recorded in maize, 58,59 sugarcane 35 and rice. 29,60,61 Under this study we have recorded around 2-3 folds higher regeneration from desiccated calli in BR10, BRRI dhan32 and BRRI dhan47 (Fig. 4, Table 3).…”
mentioning
confidence: 92%
“…27,28 An efficient plant regeneration in Bangladeshi indica rice is still poses a major problem for genetic manipulation through innovative approaches. 14,29 The optimal desiccation periods were 72 h and 48 h for Malaysian rice cultivars of MR232 and MR220 respectively, where plant regeneration enhanced up to 2-5 folds. 30 They suggested that partial desiccation can be useful in stimulating regeneration response.…”
Section: Introductionmentioning
confidence: 99%
“…According to Lee and Huang [27] , the equilibrium of cytokinin and auxin is having a significant effect in the commencement of rejuvenation of stimulated callus [27] and are believed to impact plant cell cycle and ability of morphogenesis [21] . Apart from the established role of BAP in inducing shoot multiplication [ 1 , 20 , 47 ] many workers have reported the shoot induction on auxin and cytokinin combination also [ 4 , 12 , 38 ]. As in present study highest regeneration frequency has been obtained on BAP (5.0 mg/L) and NAA (0.5 mg/L) combination, earlier some workers have also reported shoot induction on same combination [ 33 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This combination of technologies can lead to creation of novel rice types having superior quality and high crop produce as well as stress tolerance to both abiotic and biotic stress [ 19 , 42 ]. For the efficient application of biotechnology in enhancement of rice yield, successful in vitro plant regeneration is critical [4] . The in vitro growth process is a crucial step in genetic transformation and provides substrate options that might be receivers of foreign DNA [16] .…”
Section: Introductionmentioning
confidence: 99%